2014
DOI: 10.1021/ja508647u
|View full text |Cite|
|
Sign up to set email alerts
|

Reversible Interconversion of CO2 and Formate by a Molybdenum-Containing Formate Dehydrogenase

Abstract: CO2 and formate are rapidly, selectively, and efficiently interconverted by tungsten-containing formate dehydrogenases that surpass current synthetic catalysts. However, their mechanism of catalysis is unknown, and no tractable system is available for study. Here, we describe the catalytic properties of the molybdenum-containing formate dehydrogenase H from the model organism Escherichia coli (EcFDH-H). We use protein film voltammetry to demonstrate that EcFDH-H is a highly active, reversible electrocatalyst. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
200
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(208 citation statements)
references
References 28 publications
6
200
1
1
Order By: Relevance
“…This kinetic behavior is not exclusive to the Dd FDH and initial lag phases were also described with, e.g., Syntrophobacter fumaroxidans W-FDH1. 14 The lag phase extent was found to be dependent on the enzyme and formate concentrations, with shorter lag phases being obtained with higher enzyme or formate concentrations (Fig. 2, curves a-e).…”
Section: Transients During Fdh-catalyzed Formate Oxidation (Initial Lmentioning
confidence: 88%
“…This kinetic behavior is not exclusive to the Dd FDH and initial lag phases were also described with, e.g., Syntrophobacter fumaroxidans W-FDH1. 14 The lag phase extent was found to be dependent on the enzyme and formate concentrations, with shorter lag phases being obtained with higher enzyme or formate concentrations (Fig. 2, curves a-e).…”
Section: Transients During Fdh-catalyzed Formate Oxidation (Initial Lmentioning
confidence: 88%
“…Mo-FDH from E. coli is the best characterized metal dependent FDH, and easy to produce in a stable, reduced form yielding significant advantages for the EFC field. 10,13 Therefore, future work will focus on developing materials strategies for improving the performance of the Mo-FDH bioanodes for fuel cell applications.…”
Section: Discussionmentioning
confidence: 99%
“…Work by Bassegoda et al 13 and Robinson et al 15 reported the reversible interconversion of CO 2 and formate without using any mediator with the FDH adsorbed on graphite-epoxy rotating disk working electrode. While the direct electrochemical approach adopted by the authors is well-suited to study finer thermodynamic and kinetic properties of metalloenzymes (i.e., FDH), mediated electrochemical approaches facilitated by redox polymers (BPV-LPEI) are better suited for application in devices where increased enzyme loading and current densities can be realized at an electrode surface.…”
Section: -29mentioning
confidence: 99%
“…Two classes of FDHs have been discovered thus far: metal-independent nicotinamide adenine dinucleotide (NADH)-based FDHs [1,2] and metal-dependent molybdenum (Mo)-based or tungsten (W)-based FDHs [3][4][5]. We had earlier created several NADPH-dependent type FDHs and combined them with photosystem I (PSI), ferredoxin, and ferredoxin-NADP + -reductase to establish an artificial light-driven carbon dioxide reduction system (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The dimer of FdoG and FdoH is directed toward the cytoplasmic side, and with FdoH anchored to the periplasmic membrane and the FdoI subunit by a C-terminal hydrophobic domain [16]. Among these three metal-dependent FDHs from E. coli, EcFDH-H has been well-studied due to its structural simplicity and solubility [3], but it is intractable for practical applications due to its extremely high oxygen-sensitivity.…”
Section: Introductionmentioning
confidence: 99%